2004
DOI: 10.1038/sj.bmt.1704791
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR assays based on distinct genomic regions for cytomegalovirus reactivation following hematopoietic stem cell transplantation

Abstract: Summary:Real-time PCR has many advantages compared with antigenemia and qualitative PCR assays for detecting cytomegalovirus (CMV) infection in patients following SCT. However, the procedure used in each report was not standardized. This study compares the CMV load detected by real-time PCR assays amplifying distinct genomic regions. Real-time PCR assays based on US17, UL65, immediate early protein (IE) and glycoprotein B(gB) were selected and comparisons were made between each genomic region, and with antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In our study, the CMV DNA copy number determined by real-time CMV PCR using SYBR Green I correlated with the number of pp65-positive cells, in agreement with the results of other studies using a TaqMan-based assay (Gault et al 2001;Sanchez et al 2001;Leruez-Ville et al 2003;Li et al 2003;Ikewaki et al 2005). ROC analysis showed that this real-time CMV PCR exhibited adequate sensitivity and specificity, using the pp65 antigenemia assay as a reference standard.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study, the CMV DNA copy number determined by real-time CMV PCR using SYBR Green I correlated with the number of pp65-positive cells, in agreement with the results of other studies using a TaqMan-based assay (Gault et al 2001;Sanchez et al 2001;Leruez-Ville et al 2003;Li et al 2003;Ikewaki et al 2005). ROC analysis showed that this real-time CMV PCR exhibited adequate sensitivity and specificity, using the pp65 antigenemia assay as a reference standard.…”
Section: Discussionsupporting
confidence: 76%
“…Real-time PCR, one modality of quantitative PCR, is a simple, reliable, cost-effective, and time-saving alternative strategy (Holland et al 1991). Many institutes have developed real-time PCR assays for monitoring CMV, and have reported encouraging results (Gault et al 2001;Cortez et al 2003;Li et al 2003;Nitsche et al 2003;Ikewaki et al 2005), where a dual-labeled fluorogenic hybridization probe or two singlelabeled probes have been used to monitor PCR product formation.…”
mentioning
confidence: 99%
“…The differences among assays are based on the method for nucleic acid extraction, the specimen type, the target genomic region, primers and probes used for amplification and www.intechopen.com detection Ikewaki et al, 2005). Although, the variability in the results obtained with commercial assays (kits or ASRs) are proven to be lower than when using inhouse developed methods ).…”
Section: Standardization Of CMV Viral Load Quantificationmentioning
confidence: 99%
“…In the absence of standardization the current clinical guidelines recommend to each individual laboratory to establish their own viral thresholds for CMV management, (Kotton et al, 2010;Razonable & Emery, 2004), threshold that cover a wide range of viral loads varying from 200-500 copies/mL in some laboratories (Ikewaki et al, 2005;Mori et al, 2002) to 2000-5000 copies/mL in others (Humar et al, 1999).…”
Section: Standardization Of CMV Viral Load Quantificationmentioning
confidence: 99%
“…For this reason, thresholds for predicting CMV disease in preemptive programs are institution or laboratory specific and cannot be generalized. These thresholds vary from 200 -500 copies/mL in some laboratories (6,7 ) to 2000 -5000 copies/mL in others (1 ). There are several factors responsible for differences in CMV values between measurement methods.…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%